Pemberdayaan Masyarakat Pesisir Tanjungpinang Provinsi Kepulauan Riau Memanfaatkan Potensi Lokal untuk Kesejahteraan Bersama - Nazwa Feryal Kamila; Junita Mawartina; Maya Yulika; Firman Firman (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2025)
Coastal communities in Tanjungpinang have enormous local potential, such as marine products, crafts, and tourism. However, this potential has not been optimally utilized due to limited access to information, skills, and policy support. This study aims to examine the empowerment of coastal communities in Tanjungpinang City, Riau Islands Province, through the utilization of local potential to improve shared welfare. The approach used is qualitative with descriptive analysis methods, through literature reviews from various relevant sources. The results of the study show that empowerment strategies carried out through skills training, strengthening local institutions, and developing potential-based businesses such as fisheries, crafts, and community-based tourism, have succeeded in increasing community participation, household income, and opening up new job opportunities. The success of empowerment is greatly influenced by active community involvement, cross-sector support, and approaches that adapt to local conditions. However, challenges such as limited access to capital, infrastructure, and inequality in access to training are still obstacles. This study recommends the need for a more inclusive, sustainable, and social justice-based empowerment strategy so that the benefits are felt evenly by all levels of coastal communities.